Acute and Persistent Symptoms in Children With Polymerase Chain Reaction (PCR)–Confirmed Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection Compared With Test-Negative Children in England: Active, Prospective, National Surveillance. (29th November 2021) - Zavala, Maria; Ireland, Georgina; Amin-Chowdhury, Zahin; Ramsay, Mary E; Ladhani, Shamez N
Abstract: Background: Most children recover quickly after coronavirus disease 2019 (COVID-19), but some may have ongoing symptoms. Follow-up studies have been limited by small sample sizes and lack of appropriate controls. Methods: We used national testing data to identify children aged 2–16 years with a SARS-CoV-2 PCR test during 1–7 January 2021 and randomly selected 1500 PCR-positive cases and 1500 matched PCR-negative controls. Parents were asked to complete a questionnaire about the acute illness and prespecified neurological, dermatological, sensory, respiratory, cardiovascular, gastrointestinal, mental health (including emotional and behavioral well-being), and other symptoms experienced ≥5 times at 1 month after the PCR test. Results: Overall, 35.0% (859/2456) completed the questionnaire, including 38.0% (472/1242) of cases and 32% (387/1214) of controls, of whom 68% (320/472) and 40% (154/387) were symptomatic, respectively. The most prevalent acute symptoms were cough (249/859, 29.0%), fever (236/859, 27.5%), headache (236/859, 27.4%), and fatigue (231/859, 26.9%). One month later, 21/320 (6.7%) of symptomatic cases and 6/154 (4.2%) of symptomatic controls ( P  = .24) experienced ongoing symptoms. Of the 65 ongoing symptoms solicited, 3 clusters were significantly ( P  < .05) more common, albeit at low prevalence, among symptomatic cases (3–7%) than symptomatic controls (0–3%): neurological, sensory, and emotional and behavioral well-being. Mental health symptoms were reported by all groups but more frequently among symptomatic cases than symptomatic controls or asymptomatic children. Conclusions: Children with symptomatic COVID-19 had a slightly higher prevalence of ongoing symptoms than symptomatic controls, and not as high as previously reported. Healthcare resources should be prioritized to support the mental health of children. Abstract : We found a higher prevalence of acute (68% vs 40%) and ongoing symptoms at 1 month (6.7% vs 4.2%) in children with PCR-confirmed COVID-19 compared with PCR-negative symptomatic controls, but mental health symptoms were high and equally prevalent in both.